Mudanças dos dividendos e a persistência dos lucros: uma análise do conteúdo informacional - Silva, Romulo Olindo Rigon Coimbra e (2008)
This research had the main purpose to verify whether is possible to capture informational content of changes in dividends preceded by earnings changes with same sign and with opposite sign, in the brazilian capital market, between 2000 through 2006. The research has tried to verify whether the sign and the magnitude of changes in dividends are recognized by the market as an informational content regarding the persistence or not persistence of past earnings changes. Additionally, this study has tried to investigate whether the market use changes in dividends as an informational content concerning future profitability of the company. According to the results, changes in dividends are not interpreted by the brazilian capital market as informational content regarding the persistence or not persistence of past earnings changes. The sign of changes in dividends is not interpreted as an informational content regarding the persistence or not persistence of past earnings changes. The magnitude of changes in dividends is not interpreted as informational content regarding the persistence or not persistence of past earnings changes. Furthermore, the market does not use changes in dividends as information concerning future profitability of the company